Time Defendability of Ground Resistance Properties and Its Application of Vitric Tuff on the Development of Ground Enhancement Material - Jakah Jakah; Dicky Muslim; Anggoro Tri Mursito; Zufialdi Zakaria; Heri Nurohman (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2021)
Ground repair material is an essential part of the grounding system as a lightning rod to reduce the risk of lightning activity. Grounding repair materials consist of conductive and superconductive materials, commonly known as Ground Enhancement Materials (GEM). GEM has a low resistivity, very effectively supporting lightning shock energy to earth. Vitric tuff, a pyroclastic rock, is composed of an aluminosilicate (phyllosilicate) mineral group developed as a grounding improvement material. The primary purpose of this study was to determine the decrease in resistivity of vitric tuff in its development as a GEM. The research method consisted of field observations and laboratory experiments (treatment with chemical-physical activation and formulation with additives). The results showed that moisture content, SiO2/Al2O3 ratio (quartz and feldspar mineral/albite), clay mineral, crystal quality (impurities), carbon, and salt were influenced by vitric tuff resistivity. With the vitric tuff formulation and additives, the resistivity reduction is above 99%. Based on experiments, the best formulation of GEM made from tuff is 65% activated vitric tuff, 27% activated charcoal, 6% NaCl, and 2% Cement Material Cellulose. The formula produces a resistivity value of 0.0124 Ω-m, which is stable with time and meets GEM requirements (ρ ≤ 0.20 Ω-m).